9(3x-4)+63=o

Simple and best practice solution for 9(3x-4)+63=o equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(3x-4)+63=o equation:


Simplifying
9(3x + -4) + 63 = o

Reorder the terms:
9(-4 + 3x) + 63 = o
(-4 * 9 + 3x * 9) + 63 = o
(-36 + 27x) + 63 = o

Reorder the terms:
-36 + 63 + 27x = o

Combine like terms: -36 + 63 = 27
27 + 27x = o

Solving
27 + 27x = o

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + 27x = -27 + o

Combine like terms: 27 + -27 = 0
0 + 27x = -27 + o
27x = -27 + o

Divide each side by '27'.
x = -1 + 0.03703703704o

Simplifying
x = -1 + 0.03703703704o

See similar equations:

| 2x^2-x+18=0 | | 16^1/2^3 | | 2.5x=1.25x+60 | | 21-2x+5x=15+9x | | 4x^2-2x+36=0 | | Y/-15=-3 | | x^2-10x+35=7x-35 | | z^2+0.6z-20.16=0 | | -10x^2-21x+10=0 | | x^2-1.375x+0.375=0 | | 3x-9+9x=10x-5-2x | | 2(3f+4)-2=2f+6+4f | | X-3(x+1)=7 | | -4x+1=4x-7 | | -15-8= | | (d-5)(3d+4)=0 | | 5y-15-8+1y= | | -7c-3=30-4c | | 12-y=4 | | 3a+15=9a-18 | | 2n+1/6=n+1/2 | | 3x+2x+7=12 | | 5x+7=3(x-5)-2 | | e+2e+3e= | | z/5=-4 | | z+9=-6 | | 3y+y+5y= | | 9x-6=5x+18 | | 3c-5=16 | | 5b+16=8b+10 | | 9x-6=x+18 | | 9u^2-30u+25= |

Equations solver categories